Effect of Drought and Rehydration on Physiological Characteristics of Agriophyllum squarrosum (L.) Moq. in Different Habitats - Juanli Chen; Yongqing Luo; Xueyong Zhao; Yan Li; Junpeng Mu (Plants, 2024)
Agriophyllum squarrosum (L.) Moq. is a highly prevalent xerophytic species found throughout northern China. It is suitable for cultivation in semi-arid sandy environments and may establish roots in arid desert locations. This species plays a pioneering and exploratory role in the colonization of desert plants. In this study, we selected A. squarrosum from the Urat desert steppe (UD) and Horqin sandy land (HS) to explore their adaptation mechanisms to drought and rehydration environments by using the pot weighing control method to simulate an arid environment. The findings showed that the control (watering to 60–65% of field capacity) exceeded its required amount and the leaves turned yellow. The chlorophyll content was lower than those under moderate and severe drought, and rehydration caused a decrease. However, the contents of malondialdehyde, soluble sugar, and proline in the drought treatment were higher than those in the control. Under moderate and severe drought, the chlorophyll content and the quantum efficiency of photosystem II (Fv/Fm) of A. squarrosum from UD were higher than those from HS. During drought and rehydration processes, the proline content was relatively lower, while the activities of peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) and the content of soluble sugar and soluble protein were higher. However, antioxidant enzymes and osmoregulators from UD were higher than those from HS. The results suggest that the stronger ability of A. squarrosum to endure drought environments in UD is due to the high level of antioxidant enzymes and osmoregulators, which are conducive to relieving cell membrane damage when subjected to drought and rehydration.